2016
DOI: 10.4317/medoral.20183
|View full text |Cite
|
Sign up to set email alerts
|

Relation between diagnosis of atheromatous plaque from orthopantomographs and cardiovascular risk factors. A study of cases and control subjects

Abstract: BackgroundIn recent years the use of orthopantomography has been proposed as a low-cost, reliable and non-invasive diagnostic medium for detecting atheromatous plaque. The purpose of this study was to correlate the presence of carotid calcifications (atheroma) in orthopantomographs with specific risk factors for cerebrovascular accidents (previous cerebrovascular accidents, arterial hypertension, and diabetes).Material and MethodsThe methods used in this observational study of cases and control subjects follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(40 reference statements)
1
6
0
2
Order By: Relevance
“…Earlier reports have shown that the prevalence rates vary depending on the sample size and population. Specifically, Barona-Dorado et al 5 (2016) reported a prevalence of 15.4% based on 1.130 radiographs. The authors exclusively sampled Spanish patients aged >18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports have shown that the prevalence rates vary depending on the sample size and population. Specifically, Barona-Dorado et al 5 (2016) reported a prevalence of 15.4% based on 1.130 radiographs. The authors exclusively sampled Spanish patients aged >18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Обнаружена связь между кальцинатами СА и наличием основных ФР БСК: длительного стажа курения, сахарного диабета, артериальной гипертензии, гиперлипидемии [21][22][23][24][25].…”
Section: Abstract: Primary Stroke Prevention Carotid Artery Calcificunclassified
“…При системных заболеваниях (СД, дилатационная кардиомиопатия, мочекаменная болезнь и другие состояния) распространенность кальциноза СА выше, чем в общей популяции, и варьирует в диапазоне от 8,2 до 38,8% [25,32,33,38,39].…”
Section: Abstract: Primary Stroke Prevention Carotid Artery Calcificunclassified
“…Since 1981, when CCAA s were first described in panoramic radiographs (PRs), dentistry has received increasing attention (4,5). Routine dental PR was report to be a useful tool, low-cost, reliable, and noninvasive diagnostic medium method for identifying CCAAs (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…Current literature suggests that the risk of stroke should not be estimated solely on the incidental finding of CCAA on panoramic images. Other risk factors such as age, sex, history of prior stroke, obesity, diabetes mellitus, sedentary lifestyle, smoking history, total cholesterol level, rheumatoid arthritis, arterial stenosis, and hypertension should also be part of the overall risk assessment (4,6,(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%